2016
DOI: 10.1007/s00262-016-1827-4
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor effects of DNA vaccine targeting human fibroblast activation protein α by producing specific immune responses and altering tumor microenvironment in the 4T1 murine breast cancer model

Abstract: Fibroblast activation protein α (FAPα) is a tumor stromal antigen overexpressed by cancer-associated fibroblasts (CAFs). CAFs are genetically more stable compared with the tumor cells and immunosuppressive components of the tumor microenvironment, rendering them excellent targets for cancer immunotherapy. DNA vaccines are widely applied due to their safety. To specifically destroy CAFs, we constructed and examined the immunogenicity and anti-tumor immune mechanism of a DNA vaccine expressing human FAPα. This v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…Earlier, it was shown that Luc DNA immunization can induce a CTL-mediated resistance to the growth of Luc-expressing tumors 14 . In case of 4T1 tumors, an effective immune response against one of the tumor associated antigens, fibroblast activation protein α overexpressed by cancer-associated fibroblasts, successfully reduced 4T1 tumor growth, also in a CTL-mediated fashion 49 . Our data on unsuccessful Luc DNA-immunization reveals that cancer vaccine candidates can be easily compromised by an inappropriate administration mode.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, it was shown that Luc DNA immunization can induce a CTL-mediated resistance to the growth of Luc-expressing tumors 14 . In case of 4T1 tumors, an effective immune response against one of the tumor associated antigens, fibroblast activation protein α overexpressed by cancer-associated fibroblasts, successfully reduced 4T1 tumor growth, also in a CTL-mediated fashion 49 . Our data on unsuccessful Luc DNA-immunization reveals that cancer vaccine candidates can be easily compromised by an inappropriate administration mode.…”
Section: Discussionmentioning
confidence: 99%
“…The vaccine successfully reduced the growth of 4T1 tumours by producing a specific CTL response to FAPα that killed CAFs. 100 FAPα-based vaccines may be used to induce FAPαspecific CTLs to kill CAFs and destroy immunosuppressive components in the TME. 101,102 These vaccines can also reduce the risk of immune escape, which is an advantage that tumour-associated antigen (TAA) does not have.…”
Section: Anti -C An Cer-a Sso Ciated Fib Rob L a S T Ther Apie Smentioning
confidence: 99%
“…For example, Alexander et al [44] evaluated the efficacy of an allogeneic cancer cell vaccine enhanced by xenogeneic melanoma antigen in a melanoma model of pet dogs, and the vaccine resulted in an overall response rate of 17% and a cancer control rate of 35%. An early study showed that a DNA vaccine targeting hFAPa suppressed breast cancer growth by eliciting specific cellular immune responses and altering the TME in a mouse model [45]. In the present study, we modified murine tumour cells expressing hFAPa as a WCTV to break the mouse immune tolerance to FAPa.…”
Section: Discussionmentioning
confidence: 96%